AN EXPERIMENTAL MODEL OF ESOPHAGUS AND STOMACH CHEMICAL BURN WITH MODERN AGGRESSIVE CHEMICAL AGENTS - M. L. Tykhenova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Aim of the research: to explore the model of esophagus and stomach chemical burn with modern chemical agents in the experiment on animals. The article presents the results of experimental research of chemical burn of the esophagus in Vistar rats. The burn of esophagus was conducted by modern chemical agents. As the result of the research the substances with «low» and «high» degree of aggressiveness were determined.